Dualism of Words and Meanings: The Debate Among I’jāz Scholars and Classical Arabic Critics - Al-Mubassyir, Muhammad; Naf'an, Abdul Wahab (Journal of Arabic Language Studies and Teaching, 2024)
The aesthetic aspects of kalām (rhetoric or expression) have prompted extensive debate among classical Arab critics regarding the dualism of lafẓ (expression) and ma'nā (meaning). Central to this debate is whether beauty resides in the wording, the meaning, or a combination of both. This discussion became particularly pronounced in the context of the Qur'anic miraculousness, eventually leading to the development of the science of balaghah (rhetoric) between the 2nd and 5th centuries CE. This article employs a literature review and qualitative descriptive approach to examine the discourse on the dualism of lafẓ and ma'nā among scholars of i'jāz (inimitability) and classical Arab critics. The literature review incorporates primary sources from classical critics alongside modern perspectives to provide a comprehensive and nuanced understanding. The study finds that within the debate on lafẓ and ma'nā, there are proponents of lafẓ (anṣār al-lafẓ), proponents of ma'nā (anṣār al-ma’nā), and those who advocate for an integration of both. Notably, Abdul Qahir al-Jurjani presents a unique perspective through his theory of naẓm, which asserts that the beauty of kalām is derived from its arrangement in accordance with the conceptual meaning (ma’ānī fī al-nafs).